Sumatriptan as abortive treatment in cyclic vomiting syndrome: A cross-sectional study - Bixuan Lin; Zhipeng Zhou; Thangam Venkatesan (SAGE Publishing, 2020)
Cyclic vomiting syndrome (CVS) is characterized by episodic vomiting and shares similarities with migraine headache. Guidelines recommend using triptans as abortive therapy in CVS, but there are limited data on its efficacy. Methods: We thus sought to characterize sumatriptan use and performed a cross-sectional study of adults with CVS episodes within the previous 6 months. Questionnaires about demographics, clinical characteristics, and response to sumatriptan (defined as >50% reduction in symptoms) were administered via e-mail. We investigated differences between responders and nonresponders, using χ 2 and Student's t test. Results : Of 101 participants (age 41 ± 15 years, 74% female, 83% Caucasian), 39 (38%) used sumatriptan during their last CVS attack. Most reported an improvement in nausea (55%), vomiting (59%), and abdominal pain (43%) within 2 h and at 24 h (67%, 73%, and 67%) respectively. Eighteen (46%) reported that sumatriptan helped them avoid emergency department visits and 20 (51%) avoided being hospitalized. Nonresponse to sumatriptan was associated with depression ( p = 0.01), current cannabis use ( p = 0.02), use of benzodiazepines ( p = 0.04), and opioids (0.02) during an episode. No serious side effects were noted. Conclusions : Sumatriptan use reduced symptoms of CVS but did not abort them. Prospective studies to determine its independent effects are needed.